Analysis of the molecular variability of Grapevine leafroll-associated virus 1 reveals the presence of two distinct virus groups and their mixed occurrence in grapevines - Komínek, Petr; Glasa, Miroslav; Bryxiová, Marcela (Virus genes, 2005)
Genetic diversity of eight Grapevine leafroll-associated virus 1 (GLRaV-1) isolates recovered from grapevines in three distinct locations in the Czech Republic and Slovakia was characterised by restriction fragment length polymorphism (RFLP) analysis and by sequencing of cloned 540 bp fragment of the heat shock protein 70 (HSP70) gene. Comparison and phylogenetic analysis of obtained and previously available sequence data revealed the existence of two groups of GLRaV-l isolates, tentatively named A and E (genetic divergence between A and E group reached 13.9%). An RT-PCR detection method followed by simple restriction analysis was developed, showing the potential to differentiate GLRaV-1 isolates of these groups. Interestingly, a mixed infection of two GLRaV-1 groups in the same plant was frequently detected together with a high intra-group variability in some isolates.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Closteroviridae; Česká republika; polymorfismus délky restrikčních fragmentů; HSP70 Heat-Shock Proteins; DNA virů; genetická variace; Czech Republic; Cloning, Molecular; Genetic Variation; Slovakia; Vitis; sekvence nukleotidů; Base Sequence; virové geny; Slovenská republika; Viral Proteins; Amino Acid Sequence; Polymorphism, Restriction Fragment Length; fylogeneze; DNA, Viral; nemoci rostlin; klonování DNA; molekulární sekvence - údaje; virové proteiny; sekvenční homologie aminokyselin; proteiny tepelného šoku HSP70; Phylogeny; Genes, Viral; Sequence Homology, Amino Acid; Plant Diseases